Effects of ocean acidification on the swimming ability, development and biochemical responses of sand smelt larvae - Silva, Cátia Sofia Esteves da (2016)
Ocean acidification, recognized as a major threat to marine ecosystems, has developed into one of the fastest growing fields of research in marine sciences. Several studies on fish larval stages point to abnormal behaviours, malformations and increased mortality rates as a result of exposure to increased levels of CO2. However, other studies fail to recognize any consequence, suggesting species-specific sensitivity to increased levels of CO2, highlighting the need of further research. In this study we investigated the effects of exposure to elevated pCO2 on behaviour, development, oxidative stress and energy metabolism of sand smelt larvae, Atherina presbyter. Larvae were caught at Arrábida Marine Park (Portugal) and exposed to different pCO2 levels (control: ~600μatm, pH=8.03; medium: ~1000μatm, pH=7.85; high: ~1800μatm, pH=7.64) up to 15days, after which critical swimming speed (Ucrit), morphometric traits and biochemical biomarkers were determined. Measured biomarkers were related with: 1) oxidative stress - superoxide dismutase and catalase enzyme activities, levels of lipid peroxidation and DNA damage, and levels of superoxide anion production; 2) energy metabolism - total carbohydrate levels, electron transport system activity, lactate dehydrogenase and isocitrate dehydrogenase enzyme activities. Swimming speed was not affected by treatment, but exposure to increasing levels of pCO2 leads to higher energetic costs and morphometric changes, with larger larvae in high pCO2 treatment and smaller larvae in medium pCO2 treatment. The efficient antioxidant response capacity and increase in energetic metabolism only registered at the medium pCO2 treatment may indicate that at higher pCO2 levels the capacity of larvae to restore their internal balance can be impaired. Our findings illustrate the need of using multiple approaches to explore the consequences of future pCO2 levels on organisms.